PENGARUH VARIASI SUDUT BUKAAN GUIDE VANE TERHADAP KINERJA PROTOTYPE PLTMH DENGAN TURBIN KAPLAN - I Nyoman Sudiatmika; I Wayan Arta Wijaya; I Made Suartika (Program Studi Teknik Elektro UNUD, 2021)
The increase in the need for electrical energy in Indonesia is increasing along withpopulation growth. Followed by the depletion of fuels originating from fossil energy. Based ongeographic conditions, Indonesia has many rivers so that it has the potential to generateelectricity by utilizing the flow of water which is called PLTMH (Microhydro Power Plant). Inrealizing this PLTMH, one type of water turbine can be used, namely the Kaplan turbine, wherethis type of turbine works at low head conditions with large discharge. The purpose of thisresearch is to analyze the performance of the Kaplan type turbine guide vane prototype atangles of 15º, 30º, 45º, 60º, 75º, and 90º to meet the electricity demand in Indonesia. Afterbeing examined based on all the variations tested, the maximum value of the turbine rotationalspeed at an opening of 15º with the rotation values obtained before and after coupled with thegenerator were 249.5 rpm and 216.5 rpm. The value of the generator rotation before and afterthe 30 Watt load coupling is 1096.6 rpm and 999 rpm. Voltage, current, and power producedare 9,1 Volts, 0,68 Amperes, and 6,18 Watts. The resulting torque of 0,27 Nm. The greatestefficiency was obtained at a combination of the opening angle of the guide vane of 15º at2,62%.